Improving the Quality of Designing Learning and Teacher Competence Using Collaborative Supervision at SDN 20 Sitiung: Peningkatan Kualitas Mendesain Pembelajaran dan Kompetensi Guru Dengan Menggunakan Supervisi Kolaboratif di SDN 20 Sitiung - Syam Sahri (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2021)
The world of education is one sector that is always experiencing developments and changes following the times and the flow of globalization, in the world of education one that often experiences development is learning methods and learning curricula. This also affects the teacher who is the main instrument in realizing education, in facing the times and the development of the education curriculum, teachers must also always be ready to face it by continuously improving their competence as a teacher, one of which is professional competence so that they can improve the quality of good learning and excellent students. . This study aims to describe improving the quality of learning design and teacher competence by using collaborative supervision at SDN 20 Sitiung. The type of research in this research is school action research. School action research was carried out in two cycles. Each cycle follows a procedure of planning, action, observation, and reflection. The results showed that in the first cycle by obtaining an average value of 67 sufficient categories, in the second cycle there was an increase with an average value of 71 in the planning and implementation aspects with good categories. Based on the results of this study, it can be said that the application of collaborative supervision can improve the quality of learning design and teacher competence at SDN 20 Sitiung.